Predictors of Post-stroke Cognition Among Geriatric Patients: The Role of Demographics, Pre-stroke Cognition, and Trajectories of Depression - Kang, Christiana (Frontiers in Psychology, 2021)
Stroke is a prevalent disease among geriatric population, which tends to deteriorate cognitive ability and mental health. In such context, cognitive impairment and geriatric depression generate mutually deteriorating impacts on each other. Using the Health and Retirement Study, this study examined depression and cognition before, immediately after, and two years after the onset of stroke. Through latent growth mixture modelling, four different trajectories of depression were identified: resilience, recovery, emergent depression, and chronicity. We used demographics including gender, age, race, and ethnicity, activity of daily life, baseline cognition, and trajectories of depression to predict cognitive ability two years after the stroke. Both aforementioned demographic factors and pre-stroke cognition were predictive of post-stroke cognition, but the inclusion of depression trajectories further improved the predictive ability. Emergent depression and chronicity were two significant predictors of worse post-stroke cognition. This study showed the importance of considering a more specific trajectotrial interrelationship between depression and cognition in geriatric stroke patients.